Influence of TP53 Codon 72 Polymorphism Alone or in Combination with HDM2 SNP309 on Human Infertility and IVF Outcome. - Ying Chan; Baosheng Zhu; Hongguo Jiang; Jinman Zhang; Ying Luo; Wenru Tang (PLoS ONE, 2016)
To evaluate the association of the TP53 codon 72 (rs 1042522) alone or in combination with HDM2 SNP309 (rs 2279744) polymorphisms with human infertility and IVF outcome, we collected 1450 infertility women undergoing their first controlled ovarian stimulation for IVF treatment and 250 fertile controls in the case-control study. Frequencies, distribution, interaction of genes, and correlation with infertility and IVF outcome of clinical pregnancy were analyzed. We found a statistically significant association between TP53 codon 72 polymorphism and IVF outcome (52.10% vs. 47.40%, OR = 0.83, 95%CI:0.71-0.96, p = 0.01). No significant difference was shown between TP53 codon 72, HDM2 SNP309 polymorphisms, human infertility, and between the combination of two genes polymorphisms and the clinical pregnancy outcome of IVF. The data support C allele as a protective factor for IVF pregnancy outcome. Further researches should be focused on the mechanism of these associations.